Mechanical characterization of millimetric agarose spheres using a resonant technique - Yescas, J.; Mandal, P.; Sinha, J.; Snook, R.; Hawkes, J.; Moreno Garibaldi, P.; Carrera-Espinoza, R. (Archives of Mechanics, 2020)
This paper presents a methodology for the mechanical characterization of agarose millimetric spheres using resonant principles. Detection of the modes of vibration was conducted using a low-cost experimental setup based on an electret microphone adapted with a thin latex elastic membrane for the sensing stage and a piezoelectric actuator driven by a conventional transformer for the excitation stage. The identification of vibration modes is supported through an ANSYS Finite Element model of the experimental setup. Experimental and numerical results demonstrate that two modes of vibration, known as Quadrupole and Octupole, appear in the amplitude spectrum and can be used to obtain stiffness values for the samples. Following this approach, Young's modulus of 209 ± 19.80, 338 ± 35.30 and 646 ± 109 kPa for 2%, 3% and 4% agarose millimetric spheres were calculated.